The effect of environmental conditions on the occurrence of Campylobacter jejuni and Campylobacter coli in wastewater and surface waters - Strakova, Nicol; Shagieva, Ekaterina; Ovesna, Petra; Korena, Kristyna; Michova, Hana; Demnerova, Katerina; Kolackova, Ivana; Karpiskova, Renata (Journal of applied microbiology, 2022)
AIMS: The purpose of the study was to evaluate the occurrence of Campylobacter jejuni and Campylobacter coli in the aquatic environment based on the water origin, seasonality and physico-chemical properties. METHODS AND RESULTS: The occurrence of C. jejuni and C. coli was determined in waste (29) or surface (56) waters in four different seasons. The air and water temperatures were measured during sampling and chemical analyses of water samples for ammonium, chloride, chlorine, nitrite, nitrate, phosphate and iron were performed. The thermotolerant Campylobacter spp. were more frequently detected in wastewater (59%; 17 positive samples) compared to surface water (38%; 21 positive samples), with the highest rate in autumn (67% of samples positive) and with a higher C. coli occurrence than C. jejuni (31% vs. 26%). Ammonium (above 0.2 mg/L) and chloride ion concentrations (above 60 mg/L) favour C. jejuni. Similarly, C. coli occurrence in water was supported by ammonium (above 0.2 mg/L), chloride (above 60 mg/L) and in addition by phosphate ion concentrations (below 0.7 mg/L). CONCLUSIONS: Campylobacter presence in water is influenced by physico-chemical parameters such as concentrations of ammonium and chloride ions. SIGNIFICANCE AND IMPACT OF THE STUDY: Water environment is an alternative source of Campylobacter. The concentration of ammonium and chloride ions can be used as a basis for successful prediction of the potential occurrence of C. jejuni and C. coli in wastewater and surface water in future.
Keywords: chloride salts; seasons; Campylobacter Infections; waters; ammonium salts; Waste Water; Campylobacter coli; Humans; odpadní voda; kampylobakterové infekce; Wastewater; Campylobacter jejuni; lidé; Campylobacter